Influence of DMDBS on the morphology and mechanical properties of polypropylene cast films - Sreenivas, K.; Pol, Harshawardhan V.; Kumaraswamy, Guruswamy (Polymer Engineering and Science, 2011)
We investigate extrusion film casting (EFC) of polypropylene (PP) and examine the effects of varying the concentration of nucleating agent, dimethyl dibenzylidene sorbitol (DMDBS); melt temperature at the die exit; and the draw ratio. Addition of DMDBS increases the PP crystallization temperature, and consequently the PP lamellar repeat spacing. For the draw ratios explored, we do not observe any substantial orientation of iPP crystals for films of neat iPP. However, addition of DMDBS results in the formation of oriented PP crystals, with greater orientation for higher draw ratios. On cooling from the melt, a network of DMDBS nanofibers forms in the PP. We believe that flow-alignment of this DMDBS network templates the orientation of PP crystals. We observe that the tensile modulus and yield stress increase with PP crystal orientation. However, at high DMDBS concentrations (0.8%), films have poor mechanical strength due to formation of voids and defects. POLYM. ENG. SCI., 51:2013-2023, 2011. (C) 2011 Society of Plastics Engineers

Influence of macromolecular architecture on necking in polymer extrusion film casting process - Pol, Harshawardhan V.; Banik, Sourya; Azad, Lal Busher; Thete, Sumeet; Doshi, Pankaj; Lele, Ashish (30th International Conference of the Polymer-Processing-Society (PPS), 2015)
Extrusion film casting (EFC) is an important polymer processing technique that is used to produce several thousand tons of polymer films/coatings on an industrial scale. In this research, we are interested in understanding quantitatively how macromolecular chain architecture (for example long chain branching (LCB) or molecular weight distribution (MWD or PDI)) influences the necking and thickness distribution of extrusion cast films. We have used different polymer resins of linear and branched molecular architecture to produce extrusion cast films under controlled experimental conditions. The necking profiles of the films were imaged and the velocity profiles during EFC were monitored using particle tracking velocimetry (PTV) technique. Additionally, the temperature profiles were captured using an IR thermography and thickness profiles were calculated. The experimental results are compared with predictions of one-dimensional flow model of Silagy et al(1) wherein the polymer resin rheology is modeled using molecular constitutive equations such as the Rolie-Poly (RP) and extended Pom Pom (XPP). We demonstrate that the 1-D flow model containing the molecular constitutive equations provides new insights into the role of macromolecular chain architecture on film necking. D-1. Silagy, Y. Demay, and J-F. Agassant, Polym. Eng. Sci., 36, 2614 (1996).